Fenomena Trafficking in Person Di Wilayah Perbatasan Kalimantan Barat - Nikodemus Niko (Raheema, 2017)
Human Trafficking is an extraordinary crime which happened in the modern era today. In the origin first time, this crime has been exist in the centuries years ago. In Southeast Asia Human Trafficking fall in transnational crime; which is the offender take action is inter-country. In this paper discussed about Human Trafficking in women which occuring in border area between West Kalimantan, Indonesia and Serawak, Malaysia. Method used in this research is descriptive analysis by collecting data over secondary data from various field such as books, scientific journals, and others. Basically, phenomena trafficking in person on women have occured in the border area West Kalimantan in which not seen like human trafficking cases. Mode of used in this cases is the recruitment to work in household or companies in Malaysia. While actus was done by illegal agent, they are passing through illegal way. The things being factor of the occurrence of trafficking in person is education and poverty experienced by women.